The Comparison of the Baroque and Renaissance Aesthetics Paintings of â€œThe Last Supperâ€ by Caravaggio and Leonardo da Vinci - I Wayan Kun Adnyana (LP2M ISBI Bandung, 2017)
Abstract The paintings of Caravaggio’s and Leonardo da Vinci’s “The Last Supper” are two iconic art works from two maestros in different era. Caravaggio is one of the fame Baroque’s artists and da Vinci is the most famous Renaissance man, who created the same theme of painting: The Last Supper. The theme represents the story of Christ’s supper. Through an inductive view, this comparative study analyzes the aesthetic structures of both paintings, by using Feldman’s perspective (Art as Image and Idea (1967). The analysis includes visual structures: line, form, darkness-lightness; elements of organization: unity, balance, rhythm, and proportion; and elements of perception and aesthetic: empathy and a psychic distance. The result of this research discovers two different perspectives of aesthetic characteristics of Baroque and Renaissance pantings.Key words: Baroque, Caravaggio, Leonardo da Vinci, Renaissance, The Last Supper.